Al-Si BASED ALLOY INGOT AND METHOD FOR PRODUCING Al-Si BASED ALLOY INGOT
By adding Na and Sr as eutectic improvement elements to the melt of Al-Si alloy and controlling the cooling rate, the brittleness and porosity defects caused by excessive Na and Sr content when recovering Al-Si alloy is solved, and the excellent mechanical properties and improved recovery of the alloy are achieved.
Patent Information
- Application Number
- JP2023144092
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
When recycling Al-Si-based alloy materials, excessive Na and Sr content may cause the alloy to become brittle at high temperatures and easily break when hot rolling, and Sr will promote the reaction between Al and water vapor to form hydrogen, forming porosity defects in aluminum alloys.
By adding improved therapeutic materials to the melt of Al-Si alloy, including Na and Sr as eutectic improvement elements, and controlling the average cooling rate at 0.1°C/s or higher during the cooling process to reduce the Na and Sr content and inhibit the growth of eutectic silicon particles.
The excellent mechanical properties and improved recovery of Al-Si alloy are achieved, and the cracking and porosity defects during hot rolling are avoided, while maintaining the ductility and tension of the alloy.
Smart Images

Figure 2025037284000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an Al-Si based alloy ingot and a method for producing an Al-Si based alloy ingot. [Background technology]
[0002] In order to improve the mechanical properties of hypoeutectic Al-Si alloy ingots, a modifying agent is added to the molten metal before casting. The modifying agent can refine eutectic Si particles (see, for example, Patent Document 1). This can improve the ductility and toughness of the Al-Si alloy. As the modifying agent, for example, a single eutectic modifying element such as Na or Sr, or an intermediate alloy containing a eutectic modifying element is used.
[0003] Incidentally, in recent years, from the viewpoint of reducing the burden on the global environment, it has been desired to use aluminum waste materials such as discarded aluminum alloy materials and scraps of aluminum products as a casting raw material when producing aluminum alloy materials. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 6-88152 Summary of the Invention [Problem to be solved by the invention]
[0005] However, when recycling Al-Si alloy materials containing Na or Sr, or aluminum waste materials containing the Al-Si alloy materials as casting raw materials, the following problems may occur. For example, when recycling an Al-Si alloy material containing Na, the aluminum alloy material may be easily embrittled at high temperatures due to Na, and the aluminum alloy material may crack during hot rolling. In addition, when recycling an Al-Si alloy material containing Sr, the reaction between Al and water vapor in the air is easily promoted by Sr during remelting. In addition, when Al reacts with water vapor, hydrogen gas is generated. If this hydrogen gas is mixed into the molten metal, holes called porosity may be generated in the aluminum alloy material.
[0006] To avoid such problems during recycling, it is possible to simply reduce the contents of Na and Sr. However, simply reducing the contents of Na and Sr may lead to coarsening of eutectic Si particles.
[0007] The present invention has been made in view of the above background, and aims to provide an Al-Si based alloy ingot having excellent mechanical properties and improved recyclability, and a method for producing an Al-Si based alloy ingot. [Means for solving the problem]
[0008] One aspect of the present invention is A chemical composition including Si: 3.7% by mass or more and 12.6% by mass or less, and further including one or two elements selected from Na: 0 ppm by mass or more and 1 ppm by mass or less and Sr: 0 ppm by mass or more and 20 ppm by mass or less, with the balance being Al and unavoidable impurities; The number of eutectic silicon particles having a circularity of 0.5 or more and a circle equivalent diameter of 10 μm or more is 1 mm 2 The present invention relates to an Al-Si based alloy ingot having a metal structure in which the number of grains per grain is two or less.
[0009] Another aspect of the present invention is A method for producing an Al-Si alloy ingot according to the above aspect, comprising the steps of: A modification treatment material containing one or two eutectic modifying elements selected from the group consisting of Na and Sr is dissolved in a molten Al-Si alloy containing 3.7 mass% or more and 12.6 mass% or less of Si, Thereafter, the contents of the eutectic improving elements in the molten Al-Si alloy are reduced to Na: 0 ppm by mass or more and 1 ppm by mass or less, and Sr: 0 ppm by mass or more and 20 ppm by mass or less, Thereafter, the molten Al-Si alloy is cast under conditions in which the average cooling rate from a temperature 5°C higher than the solidus temperature of the molten Al-Si alloy to a temperature 5°C lower than the solidus temperature of the molten Al-Si alloy is 0.1°C / s or more. Effect of the Invention
[0010] According to one aspect of the present invention, the Al-Si alloy ingot (hereinafter sometimes referred to as "ingot") contains one or two elements selected from Na: 0 mass ppm to 1 mass ppm and Sr: 0 mass ppm to 20 mass ppm, and has a circularity of 0.5 or more and a number of eutectic Si particles having a circle equivalent diameter of 10 μm or more within 1 mm 2 Therefore, these Al-Si based alloy ingots have excellent mechanical properties and improved recyclability.
[0011] According to another aspect of the present invention, first, by dissolving an improving treatment material containing a eutectic improving element in an Al-Si alloy molten metal (hereinafter sometimes referred to as "molten metal"), it is believed that P in the molten metal is rendered harmless, and thus coarsening of eutectic Si particles can be suppressed. Next, by removing excess eutectic improving elements from the molten metal, it is believed that cracking and porosity generation during hot rolling can be suppressed when recycling an Al-Si alloy ingot. Furthermore, after reducing the content of the eutectic improving element in the molten metal to within the above-mentioned specific range, the molten metal is cast under conditions where the average cooling rate from a temperature 5°C higher than the solidus temperature of the molten metal to a temperature 5°C lower than the solidus temperature of the molten metal is 0.1°C / s or more, so that the molten metal is likely to solidify while maintaining the state in which P is rendered harmless by Na or Sr, and therefore the growth of eutectic Si particles can be suppressed. Thus, according to another aspect of the present invention, an Al-Si alloy ingot having excellent mechanical properties and improved recyclability can be obtained. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a graph showing temperature changes during solidification of the molten metal in the manufacturing process of the test materials S1 and R1 of Example 1. [Diagram 2] FIG. 2 is an enlarged photograph of eutectic Si particles contained in the ingot of the test material S1 in Example 1. [Diagram 3] FIG. 3 is an enlarged photograph of a eutectic Si particle contained in an ingot of test material R1 in Example 1. [Figure 4] FIG. 4 is an enlarged photograph of eutectic Si particles contained in the ingot of test material S3 in Example 2. [Diagram 5] FIG. 5 is an enlarged photograph of a eutectic Si particle contained in an ingot of test material R3 in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (Al-Si alloy ingot) The ingot has the specific chemical composition and the specific metal structure.
[0014] [Chemical composition] The gold ingot has a chemical composition containing Si: 3.7% by mass or more and 12.6% by mass or less, and further containing one or two elements of Na: 0 ppm by mass or more and 1 ppm by mass or less and Sr: 0 ppm by mass or more and 20 ppm by mass or less, with the remainder being Al and unavoidable impurities.
[0015] Of Na and Sr, the ingot may contain only Na, may contain only Sr, or may contain both Na and Sr.
[0016] The reason why the mechanical properties of the ingot are improved by Na or Sr is presumed to be, for example, as follows. When the ingot contains P as an impurity, P forms AlP in the molten metal. It is believed that this AlP acts as a nucleus to generate and coarsen eutectic Si particles. In contrast, when Na or Sr is added to the molten metal during the ingot manufacturing process, AlP can be changed to Na3P or Sr3P2. Since this Na3P or Sr3P2 does not have nucleation ability, it is believed that by changing AlP to Na3P or Sr3P2, the growth of eutectic Si particles can be suppressed and the ingot structure can be improved.
[0017] On the other hand, when Na or Sr is added in the manufacturing process of the ingot, excess Na or Sr that has not reacted with P may remain in the ingot. When an Al-Si alloy material containing Na or Sr is recycled as a casting raw material, as described above, if a large amount of Na remains in the aluminum alloy material, the aluminum alloy material may crack during hot rolling. In addition, if a large amount of Sr remains in the aluminum alloy material, voids called porosity may be generated in the aluminum alloy material. From the viewpoint of avoiding these problems, it is preferable that the Na concentration or Sr concentration in the Al-Si alloy ingot is low.
[0018] Therefore, even in the case where Na is added in the manufacturing process of the ingot, by setting the Na content in the ingot within the range of 0 ppm by mass or more and 1 ppm by mass or less, it is possible to suppress cracking of the aluminum alloy material during hot rolling when the ingot is recycled.
[0019] Similarly, even if Sr is added in the manufacturing process of the ingot, by setting the Sr content in the ingot in the range of 0 mass ppm or more and 20 mass ppm or less, the Si particles in the ingot can be made fine, so that the ductility and toughness of the ingot can be improved. In addition, when the ingot is recycled, the reaction between Al and water vapor due to Sr can be suppressed, so that the generation of porosity in the aluminum alloy material can be suppressed. From the viewpoint of further improving the recyclability of the ingot, the Sr content in the ingot is preferably 15 mass ppm or less, more preferably 10 mass ppm or less, further preferably 8 mass ppm or less, and particularly preferably 5 mass ppm or less. On the other hand, from the viewpoint of improving the ductility and toughness of the ingot, the Sr content is preferably 1 mass ppm or more.
[0020] In determining the preferred range of the Sr content in the ingot, the above-mentioned upper and lower limits of the Sr content in the ingot can be combined arbitrarily. For example, the preferred range of Sr may be 1 ppm by mass to 15 ppm by mass, 1 ppm by mass to 10 ppm by mass, 1 ppm by mass to 8 ppm by mass, or 1 ppm by mass to 5 ppm by mass.
[0021] The Na and Sr contained in an Al-Si based alloy ingot can be measured by a solid-state optical emission spectrometer (OES; Optical Emission Spectrometer).
[0022] The Al-Si alloy ingot may further contain one or more elements selected from the group consisting of Fe: 1% by mass or less, Cu: 0.5% by mass or less, Mg: 2.0% by mass or less, Mn: 0.85% by mass or less, Ti: 0.2% by mass or less, Cr: 0.1% by mass or less, and Zn: 0.5% by mass or less. The mechanical properties of the Al-Si alloy ingot, such as strength, corrosion resistance, and workability, can be improved according to the contained elements. Furthermore, the Al-Si alloy ingot may contain trace elements other than the above elements. Examples of trace elements contained in the Al-Si alloy ingot include B, Be, Bi, Ca, Cd, Ga, In, Li, Ni, Pb, Sn, V, Zr, and Hg. The content of the trace elements is preferably 0.05% by mass or less for each element. In addition, the total of the trace elements is preferably 0.15% by mass or less.
[0023] More specifically, the Al-Si alloy ingot may have a chemical composition containing Si: 3.7% by mass or more and 12.6% by mass or less, Fe: 1% by mass or less, Cu: 0.5% by mass or less, Mg: 2.0% by mass or less, Mn: 0.85% by mass or less, Ti: 0.2% by mass or less, Cr: 0.1% by mass or less, and Zn: 0.5% by mass or less, and further containing one or two elements of Na: 0 ppm by mass or more and 1 ppm by mass or less and Sr: 0 ppm by mass or more and 20 ppm by mass or less, with the balance being Al and unavoidable impurities.
[0024] [Metal structure] The ingot has a metal structure in which eutectic Si particles are dispersed in an Al matrix. The number of eutectic Si particles having a circularity of 0.5 or more and a circle-equivalent diameter of 10 μm or more among the eutectic Si particles contained in the ingot is 1 mm 2 The number of pieces per hit is within the range of 2 or less.
[0025] In the casting process of the ingot, eutectic Si particles having various shapes are usually formed. The greater the circularity of the eutectic Si particles and the closer their shape is to a sphere, the more likely it is that stress will be concentrated on the eutectic Si particles and they will become the base of fracture when stress is applied to the ingot. Therefore, when the circularity of the eutectic Si particles is 0.5 or more and the number of eutectic Si particles having a circle equivalent diameter of 10 μm or more is 1 mm 2 By keeping the number of eutectic Si particles within the range of 2 or less per mm, the number of places where stress is concentrated when stress is applied to the ingot is reduced, thereby improving the ductility and toughness of the ingot. 2 It is more preferable that the number of particles per unit area is within the range of 1 or less, and even more preferable that the number of particles per unit area is within the range of 0.3 or less.
[0026] The ingot may contain eutectic Si particles having a circularity of less than 0.5 or a eutectic Si particle having a circle-equivalent diameter of less than 10 μm. Since these eutectic Si particles have little effect on the ductility and toughness of the ingot, the number of eutectic Si particles having a circularity of less than 0.5 or a eutectic Si particle having a circle-equivalent diameter of less than 10 μm is not particularly limited.
[0027] The circle-equivalent diameter of the eutectic Si particle described above is a value calculated by the following method. First, a test piece is taken from inside the ingot. Next, mechanical polishing and buffing are performed, and then an enlarged photograph of the eutectic Si particle is obtained by observing it under an optical microscope in normal light. The circle-equivalent diameter of each eutectic Si particle is calculated based on the projected area of the eutectic Si particle in the obtained enlarged photograph. In addition, in order to calculate the circularity described later, the length of the major axis and the length of the minor axis are calculated when each eutectic Si particle is approximated to an ellipse based on the projected area of the eutectic Si particle.
[0028] Specifically, the circularity of the eutectic Si particles described above is a value calculated by the following method. First, an enlarged photograph of the eutectic Si particle is obtained in the same manner as in the calculation of the circle equivalent diameter. In this embodiment, ImageJ, which is a public domain image processing software, is used. In addition, Trainable Weka Segmentation, a Fiji plug-in that combines a series of machine learning algorithms with a set of selected image features to generate pixel-based segmentation, is used. The images used for analysis are 50x optical microscope images, and 12 images are used for one sample. The total area of the 12 images is 54.4 mm 2 Training image data is extracted from the image data, and an AI is made to learn the structure of the metallographic structure to generate a knowledge model. The generated knowledge model is applied to the test image data. Eutectic Si particles are extracted using the knowledge model, and the extracted eutectic Si particles are binarized and only the eutectic Si particles are colored black. ImageJ is used to calculate the circle equivalent diameter, area, and circularity of the extracted eutectic Si particles. Circularity is calculated as the area S [μm 2 ] and the length of the main axis M [μm] when the eutectic Si particle is approximated as an ellipse, and is expressed by the following formula. Circularity = (4 × S) / (π × M 2 ) Using ImageJ, extract the number of eutectic Si particles of a given size.
[0029] The eutectic Si particles according to the present embodiment are relatively close to spherical, and therefore the accuracy of the calculation of the circularity can be improved by calculating the circularity based on the length M of the main axis when the eutectic Si particle is approximated to an ellipse.
[0030] (Method of manufacturing Al-Si alloy ingots) In the method for producing an Al-Si alloy ingot, A modification treatment material containing one or two eutectic modifying elements selected from the group consisting of Na and Sr is dissolved in a molten Al-Si alloy containing 3.7 mass% or more and 12.6 mass% or less of Si, Thereafter, the contents of the eutectic improving elements in the molten Al-Si alloy are reduced to Na: 0 ppm by mass or more and 1 ppm by mass or less, and Sr: 0 ppm by mass or more and 20 ppm by mass or less, Then, the Al-Si alloy molten metal is cast under conditions in which the average cooling rate from a temperature 5°C higher than the solidus temperature of the Al-Si alloy molten metal to a temperature 5°C lower than the solidus temperature is 0.1°C / s or more.
[0031] The chemical composition of the molten Al-Si alloy used in the manufacturing method may be appropriately set according to the chemical composition of the ingot to be obtained. For example, the molten metal may have a chemical composition containing Si: 3.7 mass% or more and 12.6 mass% or less, with the balance being Al and unavoidable impurities. The molten metal may further contain one or more elements selected from the group consisting of Fe: 1 mass% or less, Cu: 0.5 mass% or less, Mg: 2.0 mass% or less, Mn: 0.85 mass% or less, Ti: 0.2 mass% or less, Cr: 0.1 mass% or less, and Zn: 0.5 mass% or less as optional components. Furthermore, the Al-Si alloy ingot may contain trace elements other than the above elements. Examples of trace elements contained in the Al-Si alloy ingot include B, Be, Bi, Ca, Cd, Ga, In, Li, Ni, Pb, Sn, V, Zr, Hg, etc. The content of each trace element is preferably 0.05% by mass or less, and the total content of the trace elements is preferably 0.15% by mass or less.
[0032] In the manufacturing method, a modification agent containing a eutectic modifying element is dissolved in the molten metal. In this case, the modification agent is added so that the amount of the eutectic modifying element added is in excess of the P in the molten metal, thereby more reliably suppressing the coarsening of eutectic Si particles. From the viewpoint of suppressing the generation of coarse eutectic Si particles, the amount of the eutectic modifying element added to the molten metal is preferably 150 mass ppm or more and 250 mass ppm or less. By adding the amount of the eutectic modifying element added to the molten metal preferably 150 mass ppm or more, more preferably 180 mass ppm or more, and even more preferably 190 mass ppm or more, a sufficient amount of the eutectic modifying element can be added. In addition, by adding the amount of the eutectic modifying element added to the molten metal preferably 250 mass ppm or less, more preferably 230 mass ppm or less, and even more preferably 210 mass ppm or less, the step of reducing the content of the eutectic modifying element can be saved.
[0033] In determining the preferred range of the amount of the eutectic improving element, the upper and lower limits of the amount of the eutectic improving element can be combined arbitrarily. For example, the preferred range of the eutectic improving element may be 180 ppm by mass to 230 ppm by mass, or 190 ppm by mass to 210 ppm by mass.
[0034] In the above-mentioned manufacturing method, after dissolving the modification material in the molten metal, P in the molten metal is reacted with the eutectic modifying element. At this time, the reaction between P and the eutectic modifying element can be promoted, for example, by stirring the molten metal in which the modification material has been dissolved. From the viewpoint of sufficiently reacting P with the eutectic modifying element, it is sufficient that the time from dissolving the modification material in the molten metal to reducing the content of the eutectic modifying element is, for example, 5 minutes or more.
[0035] After dissolving the improving treatment material in the molten metal, the eutectic improving elements added in excess relative to P are reduced so that the contents of the eutectic improving elements in the molten metal are 0 ppm by mass or more and 1 ppm by mass or less of Na and 0 ppm by mass or less and 20 ppm by mass or less of Sr. Since the excess eutectic improving elements are removed from the molten metal by this process, when the ingot is recycled as a casting raw material, the recycled aluminum alloy material can be prevented from cracking or from generating porosity during hot rolling.
[0036] The method for reducing the content of the eutectic improving element in the molten metal may take various forms. For example, in the manufacturing method of the ingot, after the improving treatment material is melted, a dross forming material that reacts with the eutectic improving element to form dross may be added to the molten metal, and then the dross containing the eutectic improving element may be removed from the molten metal, thereby reducing the content of the eutectic improving element. As described above, the content of the eutectic improving element can be reduced by the simple method of adding a dross forming material to the molten metal and removing the formed dross from the molten metal.
[0037] The dross forming material is not particularly limited, and may be, for example, a flux containing one or more selected from the group consisting of KCl, MgCl2, AlF3, and K3AlF6, Cl2 gas, etc. Na or Sr contained in the molten metal reacts with the dross forming material to generate halides such as NaCl, NaF, SrCl2, and SrF2. Since the specific gravity of these halides is smaller than that of the molten metal, they rise to the surface of the molten metal to form dross. By removing this dross from the molten metal, the content of the eutectic improving element in the molten metal can be reduced.
[0038] After the content of the eutectic improving element in the molten metal is reduced to the above-mentioned specific range, the molten metal is cast under the condition that the average cooling rate from a temperature 5°C higher than the solidus temperature of the molten metal to a temperature 5°C lower than the solidus temperature is 0.1°C / s or more, thereby suppressing the growth of eutectic Si particles. This is considered to be because the molten metal is cooled at a relatively fast cooling rate as described above near the solidus temperature, so that the molten metal is likely to solidify while maintaining the state in which P is rendered harmless by Na or Sr. From the same viewpoint, the average cooling rate is more preferably 0.25°C / s or more, and even more preferably 0.5°C / s or more. Note that the term "solidus temperature" used in this specification is used in its usual sense, that is, the temperature below which a substance is completely solid (i.e., the Al-Si alloy molten metal solidifies).
[0039] The method of obtaining the solidus temperature is not particularly limited. For example, the solidus temperature may be calculated based on the composition of the target Al-Si alloy using known simulation software such as JMatPro (registered trademark) manufactured by Sente Software. The solidus temperature of the target molten Al-Si alloy may also be measured by a known method such as AA-TP1 (Standard Test Procedure for Aluminum Alloy Grain Refiners; TP-1 test). However, when the solidus temperatures obtained by multiple methods are different, such as when the actual measured value is unclear, the solidus temperature obtained by the above-mentioned JMatPro is used. EXAMPLES
[0040] Examples of the Al-Si based alloy ingot and its manufacturing method will be described below.
[0041] Example 1 In this example, an example of an Al-Si alloy ingot and its manufacturing method will be described in which Na is used as a eutectic improving element. The Al-Si alloy ingot of this example has a chemical composition containing 3.7% by mass to 12.6% by mass of Si and 0 ppm by mass to 1 ppm by mass of Na, with the balance being Al and unavoidable impurities, and has a circularity of 0.5 or more and a number of eutectic Si particles with a circle equivalent diameter of 10 μm or more that is 1 mm 2 and a metal structure in which the number of particles per one particle is two or less. Table 1 shows an example of an Al-Si alloy ingot of this example. Test material S1 and test material S2 shown in Table 1 can be obtained, for example, by the following manufacturing method.
[0042] [Test material S1] In producing the test material S1, first, 90 mass% aluminum and 10 mass% Si are melted in a crucible to prepare an Al-Si alloy melt at 750° C. The temperature of the Al-Si alloy melt is increased to 720° C., and then 200 mass ppm of metallic Na is added to the Al-Si alloy melt as an improving treatment material.
[0043] After adding the improvement treatment material to the molten Al-Si alloy, the temperature of the molten Al-Si alloy is kept at 720°C and the molten Al-Si alloy is stirred with a graphite rod for 5 minutes to fully dissolve the improvement treatment material.
[0044] After the second stirring is completed, 2200 mass ppm of a dross forming material (Promag F, manufactured by Pyrotech Japan Co., Ltd.) is added to the Al-Si alloy melt. Promag F contains KCl and MgCl2.
[0045] After adding the dross-forming material to the molten Al-Si alloy, the molten Al-Si alloy is stirred with a graphite rod for 3 minutes while maintaining the temperature of the molten Al-Si alloy at 720°C, and the dross-forming material is fully dissolved. In this manner, the dross-forming material reacts with the excess eutectic improver element to form dross containing the eutectic improver element. The dross generated on the surface of the molten Al-Si alloy is then removed by a known method, thereby reducing the content of the eutectic improver element in the molten Al-Si alloy.
[0046] After removing the dross, an iron ladle conforming to the AA-TP1 standard is immersed in the molten Al-Si alloy, and the cup of the ladle is filled with the molten metal. Then, 10 minutes after the eutectic improver is added, the ladle is pulled out of the molten Al-Si alloy, and the molten metal is scooped into the cup. The cup of the ladle is then water-cooled to solidify the molten metal. When the molten metal is solidified in this way, the average cooling rate from a temperature 5°C higher than the solidus temperature of the molten metal to a temperature 5°C lower than the solidus temperature of the molten metal is 1°C / s. The solidus temperature of the test material S1 is 577°C. The solidus temperature is measured based on the TP-1 test described above.
[0047] The temperature change of the molten metal when casting the test material S1 is shown by a solid line in Fig. 1. In Fig. 1, the dashed line L1 indicates the solidus temperature of the molten metal, the dashed line L2 indicates a temperature 5°C higher than the solidus temperature of the molten metal, and the dashed line L3 indicates a temperature 5°C lower than the solidus temperature of the molten metal.
[0048] As a result of the above, an ingot of the test material S1 is obtained. The ingot is formed into a truncated cone shape.
[0049] [Test material S2] The method for producing the test material S2 was the same as the method for producing the test material S1, except that the content of the eutectic improving elements was reduced so that the content of Na in the ingot was 0 ppm by mass.
[0050] [Test material R1] Test material R1 shown in Table 1 is a test material for comparison with test material S1 and test material S2. The method of producing test material R1 is the same as that of test materials S1 and S2, except that the average cooling rate from a temperature 5°C higher than the solidus temperature of the molten Al-Si alloy to a temperature 5°C lower than the solidus temperature of the molten alloy was 0.04°C / s. In Figure 1, the temperature change of the molten alloy when casting test material R1 is shown by a dashed line.
[0051] [Test material R2] Test material R2 shown in Table 1 is a test material for comparison with test material S1 and test material S2. The method for producing test material R2 is the same as the method for producing test material S1 and test material S2, except that no dross-forming material is added to the molten Al-Si alloy, and the molten alloy is cast after adding the improvement treatment material to the molten alloy.
[0052] (Circularity and equivalent circle diameter) The calculation method for the circularity and circle equivalent diameter of eutectic Si particles in the Al-Si alloy ingots of test materials S1, S2, and R1, R2 is as follows. Table 1 shows these values for the ingots of test materials S1, S2, and R1, R2.
[0053] The aluminum alloy is cut at a cross section 38 mm high from the small diameter surface (i.e., the surface that was in contact with the bottom surface of the ladle) of the circular end surface of the gold ingot, to expose the cut surface. After mechanically polishing and buffing the cut surface, an optical microscope is used to observe the cut surface in normal light to obtain an enlarged photograph of the eutectic Si particles. As an example, FIG. 2 shows an enlarged photograph of a eutectic Si particle 10 contained in the gold ingot of the test material S1, and FIG. 3 shows an enlarged photograph of a eutectic Si particle 10 contained in the ingot of the test material R1. As shown in FIG. 2 and FIG. 3, the eutectic Si particle 10 contained in the gold ingot has a darker color than the Al matrix 11. In addition, when the test material S1 and the test material R1 are compared, it can be seen that the test material R1 shown in FIG. 3 contains larger eutectic Si particles than the test material S1 shown in FIG. 2.
[0054] Using image analysis software (ImageJ), the area of the eutectic Si particles in the enlarged photograph is calculated, and then the circle equivalent diameter of each eutectic Si particle is calculated based on the area of the eutectic Si particles.
[0055] In addition, the lengths of the major and minor axes of the eutectic Si particles in the enlarged photograph are calculated using image analysis software, and the circularity of each eutectic Si particle is calculated from the area of the eutectic Si particle and the length of the major axis of the eutectic Si particle.
[0056] Using image analysis software, the number of eutectic Si particles in the enlarged photograph that have a circularity of 0.5 or more and a circle equivalent diameter of 10 μm or more is counted. Table 1 shows the 1 mm diameter of eutectic Si particles in each Al-Si alloy ingot. 2 Indicates the number of winning pieces.
[0057] (Eutectic improving elements remaining in Al-Si alloy ingots) In addition, the concentration of Na remaining in the Al-Si alloy ingots of test materials S1, S2 and test materials R1, R2 is measured as follows. That is, the molten metal of the test material is sampled from inside the crucible, and a button-shaped button sample is made from this molten metal. The button sample is machined to form an analysis surface. The Na concentration is measured by performing optical emission analysis on this analysis surface. The analysis is performed using a solid-state optical emission spectrometer. Specifically, an ARL4460 from Thermo Fisher Scientific is used. The results are shown in Table 1.
[0058] [Table 1]
[0059] As shown in Table 1, the Al-Si alloy ingots of the test materials S1 and S2 contain Na: an element in the range of 0 mass ppm to 1 mass ppm, have a circularity of 0.5 or more, and have a number of eutectic Si particles with a circle equivalent diameter of 10 μm or more within 1 mm 2Therefore, these Al-Si based alloy ingots have excellent mechanical properties and can suppress cracking of the recycled aluminum material during hot rolling.
[0060] The Al-Si alloy ingots of the test materials S1 and S2 are obtained by casting the molten Al-Si alloy under conditions where the average cooling rate from a temperature 5°C higher than the solidus temperature of the molten Al-Si alloy to a temperature 5°C lower than the solidus temperature of the molten Al-Si alloy is 0.1°C / s or more. Therefore, the amount of residual Na can be reduced while suppressing the generation of coarse Si particles.
[0061] The number of eutectic Si particles having a circularity of 0.5 or more and a circle equivalent diameter of 10 μm or more contained in the Al-Si alloy ingot of the test material R1 is greater than the specific range, and therefore the Al-Si alloy ingot of the test material R1 has poor machinability and poor ductility.
[0062] In addition, the Al-Si alloy ingot of the test material R2 contains 39.5 mass ppm of Na, which is larger than the specific range, and therefore the aluminum material after recycling the Al-Si alloy ingot of the test material R2 is prone to cracking during hot rolling.
[0063] Example 2 In this example, an example of an Al-Si alloy ingot using Sr as a eutectic improving element and a manufacturing method thereof will be described. Table 2 shows an example of an Al-Si alloy ingot of this example. Test materials S3 to S5 shown in Table 2 can be obtained, for example, by the following manufacturing method.
[0064] [Test materials S3 to S5] The method for producing test materials S3 to S5 is the same as the manufacturing method for test material S1, except that an intermediate alloy containing Sr is used as the improvement treatment material, and the improvement treatment material is added to the molten Al-Si alloy so that the concentration of Sr atoms in the molten alloy is 200 ppm by mass.
[0065] [Test material R3] Test material R3 is a test material for comparison with test materials S3 to S5. The manufacturing method of test material R3 is the same as that of test materials S1 and S2, except that the average cooling rate from a temperature 5°C higher than the solidus temperature of the Al-Si alloy molten metal to a temperature 5°C lower than the solidus temperature of the molten metal is 0.04°C / s.
[0066] [Test material R4] Test material R4 is a test material for comparison with test materials S3 to S5. The manufacturing method of test material R4 is the same as that of test materials S1 and S2, except that after adding the improvement treatment material to the molten Al-Si alloy, the molten alloy was cast without adding the dross forming material to the molten alloy.
[0067] (Circularity and equivalent circle diameter) The circularity and circle equivalent diameter of the eutectic Si particles in the Al-Si alloy ingots of the test materials S3 to S5 and the test materials R3 and R4 were calculated, and the number of eutectic Si particles having a circularity of 0.5 or more and a circle equivalent diameter of 10 μm or more among the eutectic Si particles was counted, and the number of eutectic Si particles is shown in Table 2. Fig. 4 shows an enlarged photograph of a eutectic Si particle 10 contained in the Al-Si alloy ingot of the test material S3, and Fig. 5 shows an enlarged photograph of a eutectic Si particle 10 contained in the ingot of the test material R3.
[0068] (Eutectic improving elements remaining in Al-Si alloy ingots) The concentrations of Sr remaining in the Al-Si based alloy ingots of the test materials S3 to S5 and the test materials R3 and R4 were measured using a solid-state emission spectrometer. The results are shown in Table 2.
[0069] [Table 2]
[0070] As shown in Table 2, the Al-Si alloy ingots of the test materials S3 to S5 contain Sr: an element in the range of 0 mass ppm to 20 mass ppm, have a circularity of 0.5 or more, and have a number of eutectic Si particles with a circle equivalent diameter of 10 μm or more within 1 mm 2Therefore, these Al-Si based alloy ingots have excellent mechanical properties and can suppress the generation of porosity in the aluminum material after recycling.
[0071] The Al-Si alloy ingots of test materials S3 to S5 are cast under conditions in which the average cooling rate from a temperature 5°C higher than the solidus temperature of the molten Al-Si alloy to a temperature 5°C lower than the solidus temperature of the molten alloy is 0.1°C / s or more. Therefore, the generation of coarse Si particles is suppressed, and the amount of remaining Sr is reduced, thereby improving recyclability.
[0072] The number of eutectic Si particles having a circularity of 0.5 or more and a circle equivalent diameter of 10 μm or more contained in the Al-Si alloy ingot of the test material R3 is greater than the specific range, and therefore the Al-Si alloy ingot of the test material R3 has poor machinability and poor ductility.
[0073] In addition, the Al-Si alloy ingot of the test material R4 contains 151 mass ppm of Sr, which is higher than the specific range. Therefore, the aluminum material after recycling the Al-Si alloy ingot of the test material R4 has porosity.
[0074] The present invention is not limited to the above-described embodiments, and can be applied to various embodiments without departing from the gist of the present invention. [Explanation of symbols]
[0075] 10 Eutectic Si particles 11 Al matrix
Claims
1. A chemical composition including Si: 3.7% by mass or more and 12.6% by mass or less, and further including one or two elements selected from Na: 0 ppm by mass or more and 1 ppm by mass or less, and Sr: 0 ppm by mass or more and 20 ppm by mass or less, with the balance being Al and unavoidable impurities; The number of eutectic Si particles having a circularity of 0.5 or more and a circle equivalent diameter of 10 μm or more is 1 mm 2 and a metal structure in which the number of particles per one particle is two or less.
2. The number of the eutectic Si particles having a circularity of 0.5 or more and a circle equivalent diameter of 10 μm or more is 1 mm 2 The Al-Si alloy ingot according to claim 1, wherein the number of particles per one ingot is 0.3 or less.
3. The Al-Si alloy ingot according to claim 1, wherein the Sr content is 1 ppm by mass or more and 20 ppm by mass or less.
4. The Al-Si alloy ingot according to claim 1, further comprising one or more elements selected from the group consisting of Fe: 1% by mass or less, Cu: 0.5% by mass or less, Mg: 2.0% by mass or less, Mn: 0.85% by mass or less, Ti: 0.2% by mass or less, Cr: 0.1% by mass or less, and Zn: 0.5% by mass or less.
5. A method for producing an Al-Si alloy ingot according to any one of claims 1 to 4, comprising the steps of: A modification treatment material containing one or two eutectic modifying elements selected from the group consisting of Na and Sr is dissolved in a molten Al-Si alloy containing 3.7 mass% or more and 12.6 mass% or less of Si, Thereafter, the contents of the eutectic improving elements in the molten Al-Si alloy are reduced to Na: 0 ppm by mass or more and 1 ppm by mass or less, and Sr: 0 ppm by mass or more and 20 ppm by mass or less; Then, the molten Al-Si alloy is cast under conditions in which an average cooling rate from a temperature 5° C. higher than a solidus temperature of the molten Al-Si alloy to a temperature 5° C. lower than the solidus temperature of the molten Al-Si alloy is 0.1° C. / s or more.
6. 6. The method for producing an Al-Si alloy ingot according to claim 5, wherein the amount of the eutectic improving element added to the molten Al-Si alloy is 150 ppm by mass or more and 250 ppm by mass or less.
7. After the improving treatment material is melted, a dross forming material that reacts with the eutectic improving element to form dross is added to the molten Al-Si alloy; 6. The method for producing an Al-Si alloy ingot according to claim 5, further comprising the steps of: removing the dross containing the eutectic modifier from the molten Al-Si alloy to thereby reduce the content of the eutectic modifier.
Citation Information
Patent Citations
Method for deciding improvement treatment of molten aluminum alloy
JP1994088152A